Natural history of anterior knee pain: a 14- to 20-year follow-up of nonoperative management. - Nimon, G; Murray, D; Sandow, M; Goodfellow, J (1998)
We describe a consecutive series of girls with idiopathic anterior knee pain in adolescence and who were treated nonoperatively. At a mean follow-up of 16 years, 22% had no pain, 71% thought that their symptoms were better than at presentation, 88% used analgesics rarely or not at all, and 90% continued to participate regularly in sports. Nevertheless, about one in four of the patients continued to have significant symptoms for < or = 20 years after presentation. No features were identified that predicted those patients in whom symptoms would persist. We conclude that surgical treatment of idiopathic anterior knee pain in adolescents is not justified until a procedure has been shown to provide a better outcome than that reported here or until a way has been found to distinguish the few patients who will not get better spontaneously from the majority who will.